2010
DOI: 10.1021/jo100941f
|View full text |Cite
|
Sign up to set email alerts
|

4-Bis(methylthio)methylene-2-phenyloxazol-5-one: Versatile Template for Synthesis of 2-Phenyl-4,5-functionalized Oxazoles

Abstract: 4-Bis(methylthio)methylene-2-phenyloxazol-5-one has been shown to be a versatile template for the synthesis of various 2-phenyl-3,4-substituted oxazoles via nucleophilic ring-opening of oxazolone with various oxygen, nitrogen, and carbon nucleophiles and subsequent 5-endo cyclization of the resulting acyclic adducts in the presence of silver carbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…136 Recently, Ila and co-workers reported a novel route to 2,3-substituted benzo[b]thiophenes 225 by intramolecular radical cyclization of polarized ketene dithioacetals 224 derived from o-bromoarylacetonitriles (Scheme 66, with the synthesis of 5,6-dimethoxy-2-(methylthio)benzo[b]thiophene-3-carbonitrile as an example). 137,138 In addition, the demethylation process via Csp 3 -S bond cleavage of the ketene dithioacetal moiety, for example, in the preparation of 2-(methylthio)thiophene-4-aldehyde 229 obtained upon treatment of 1-bis(methoxy)-4-bis(methylthio)-3-buten-2-one 228 under Simmons-Smith conditions (Scheme 67) 139 and in the preparation of the thiazole derivative 232 starting from 2-phenyl-4-bis(methylthio)methyleneoxazol-5-one (230) 140 was also observed (Scheme 68). 141…”
Section: Synthetic Applications Via Csp 3 -S Bond Cleavagementioning
confidence: 99%
See 1 more Smart Citation
“…136 Recently, Ila and co-workers reported a novel route to 2,3-substituted benzo[b]thiophenes 225 by intramolecular radical cyclization of polarized ketene dithioacetals 224 derived from o-bromoarylacetonitriles (Scheme 66, with the synthesis of 5,6-dimethoxy-2-(methylthio)benzo[b]thiophene-3-carbonitrile as an example). 137,138 In addition, the demethylation process via Csp 3 -S bond cleavage of the ketene dithioacetal moiety, for example, in the preparation of 2-(methylthio)thiophene-4-aldehyde 229 obtained upon treatment of 1-bis(methoxy)-4-bis(methylthio)-3-buten-2-one 228 under Simmons-Smith conditions (Scheme 67) 139 and in the preparation of the thiazole derivative 232 starting from 2-phenyl-4-bis(methylthio)methyleneoxazol-5-one (230) 140 was also observed (Scheme 68). 141…”
Section: Synthetic Applications Via Csp 3 -S Bond Cleavagementioning
confidence: 99%
“…For example, intramolecular annulation of a-carbamoyl ketene dithioacetals via PIFA-mediated N-S bond formation to give substituted isothiazol-3(2H)-ones (PIFA: phenyliodine(III) bis(trifluoroacetate)), 202 synthesis of 2-benzylthio-5-phenyl-3,4-disubstituted thiophenes through intramolecular condensation of a-oxo ketene dibenzylthioacetals, 203 synthesis of N-aryl-substituted 3,4-dihydro-2-pyridones from TiCl 4 -Et 3 N promoted cyclization of 2-(2-acetyl-1-methyl-3-oxobutyl)-N-aryl-3,3-bis(ethylthio)acrylamides, 204 and the synthesis of 2,3,5-trisubstituted furans 367 from a-formyl ketene dithioacetals 77 (Scheme 28) via Wittig reaction (to give 366) and subsequent NBS-mediated cyclization (Scheme 95, NBS: N-bromosuccinimide) are known. 140,205,206…”
Section: Intramolecular Cyclizationmentioning
confidence: 99%
“…89,90 Enamides 244 can be prepared in 2-steps from readily available starting materials and give the corresponding oxazoles 245 in excellent yield (74-98%). 89,90 Enamides 244 can be prepared in 2-steps from readily available starting materials and give the corresponding oxazoles 245 in excellent yield (74-98%).…”
Section: Scheme 69 Ag(i)-catalysed Synthesis Of Oxazoles 240mentioning
confidence: 99%
“…Transformation of N-(2-halovinyl)amides (isolated or generated in situ) to oxazoles could be achieved by using organic or inorganic bases, [24][25][26][27] which, nevertheless, were limited by scope of the substrates and/or efficiency of the transformation. Recently, Ila et al developed the synthesis of 2,4,5substituted oxazoles from N-(2-methylthiovinyl)benzamides mediated by Ag 2 CO 3 28 or catalyzed by CuI. 29 In addition, Glorius et al reported copper-catalyzed coupling of primary amides with 1,2-dihalogenated olefins to synthesize 2,4-and 2,5-substituted oxazoles in 2007.…”
Section: Introductionmentioning
confidence: 99%